2023
DOI: 10.1590/1519-6984.244551
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and toxicological evaluation of Origanum vulgare: an in vivo study

Abstract: Origanum vulgare has been of great interest in academia and pharma industry due to its antioxidant, antifungal and antitumor properties. The present study aimed to find the anti-MRSA potential and in vivo toxicity assessments of O. vulgare. O. vulgare extract was used to monitor anti-MRSA activity in mice. Following MRSA established infection in mice (Mus musculus), treatment with O. vulgare was continued for 7 days. Autopsies were performed and re-isolation, gross lesion scoring and bacterial load in various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…In vivo using Swiss albino mice In vivo acute oral toxicity testing did not show any toxic effects [115] Origanum vulgare In vivo using mice Continuous use or high doses may deliver undesirable components causing liver and renal function impairment [157] Thymus vulgaris In vivo using albino Holtzman rats While the 28-day oral toxicity test indicated that the no-observed-adverse-effect level (NOAEL) was more than 250 mg/kg/day, Thymus vulgaris had moderate oral toxicity.…”
Section: Symplocos Racemosamentioning
confidence: 99%
“…In vivo using Swiss albino mice In vivo acute oral toxicity testing did not show any toxic effects [115] Origanum vulgare In vivo using mice Continuous use or high doses may deliver undesirable components causing liver and renal function impairment [157] Thymus vulgaris In vivo using albino Holtzman rats While the 28-day oral toxicity test indicated that the no-observed-adverse-effect level (NOAEL) was more than 250 mg/kg/day, Thymus vulgaris had moderate oral toxicity.…”
Section: Symplocos Racemosamentioning
confidence: 99%
“…A 90-day oral toxicity study of oregano essential oil in rats revealed that up to 200 mg/kg had no adverse effects on food/water consumption, body weight, hematology, biochemistry, organ weight, and histopathology [205]. A higher dose of Origanum vulgare extracts at 400 mg/kg, however, caused hepatotoxicity, including cellular degeneration and distortion, inflammatory infiltration, cytoplasmic vacuolization, sinusoidal congestion, and apoptosis in a 7-day study in mice [206].…”
Section: The Toxicity and Safety Of Ginger Origanum Vulgare And Syzyg...mentioning
confidence: 99%
“…(Hamidpour et al 2014;Zielińska et al 2014;Bozin et al 2017;Ivanov et al 2019;Mahmood et al 2020;Ghasempour et al 2022;Najafi et al 2022;Batiha et al 2023). Most species of the family Lamiaceae have been studied on chemical, pharmacological, ethnobotanic, clinical, ecological properties, etc., since they contain many different biologically active substances (Tahir et al 2018;Kompelly et al 2019;Soltani et al 2020;Tundis et al 2020;Liaqata et al 2023). The flora of Uzbekistan has 40 genera and 206 species of plants of the Lamiaceae family (Flora of Uzbekistan, 1961).…”
Section: Introductionmentioning
confidence: 99%